Scaling up Pediatric HIV Testing by Incorporating Provider-Initiated HIV Testing Into all Child Health Services in Hurungwe District, Zimbabwe. (1st January 2018) - Musarandega, Reuben; Mutede, Blessing; Mahomva, Agnes; Nyamayaro, Wenceslas; Mushavi, Angela; Lindan, Christina; Machekano, Rhoderick
Abstract : Background: Practical ways are needed to scale-up pediatric HIV testing in sub-Saharan Africa, where testing is usually limited to HIV-exposed children in maternal and child health clinics. Methods: We implemented an enhanced pediatric HIV testing program in 33 health facilities in Zimbabwe by integrating HIV testing into all pediatric health services. We collected individual data on children tested by having health care workers complete a program-specific child health booklet. We compared numbers of children tested before and during the program using routinely collected aggregate program data reported by health facilities. Results: A total of 12, 556 children aged 0–5 years were recorded in child health booklets; 9431 (75.1%) had information on HIV testing, of whom 7326 (77.7%) were tested; 7167 had test results of whom 122 (1.7%) were HIV-infected. Among children seen in outpatient clinics, 82.1% were tested compared with 66.5% tested among children seen in maternal/child health clinics. Of the 122 HIV-infected children identified, 77 (63.1%) could be missed under existing pediatric testing guidelines. The number of HIV-infected children identified during the 6-month program increased by 55% compared with the prior 6-month period (RR = 1.55, 95% CI: 1.22 to 1.96). Factors independently associated with HIV infection included being malnourished (adjusted odds ratio [AOR] = 7.7, 95% CI: 2.1 to 28.6), being exposed to TB (AOR = 8.1, 95% CI: 2.0 to 32.2), and having an HIV-infected mother (AOR = 41.6, 95% CI: 15.9 to 108.8). Conclusions: Integrating HIV testing into all pediatric health services is feasible and can assist in identifying HIV-infected children who could be missed in current testing guidelines.